Fitossociologia de comunidades arbóreas em savanas do Brasil central - Finger, Zenesio (2008)
These studies were undertaken in the state of Mato Grosso, Brazil, in the area of Chapada dos Guimarães and Baixada Cuiabana, which are constituted of a high plateau and a big low plain, respectively, being limited to two areas covered by vegetation with a savannic physiognomy, type Cerrado stricto sensu. Considering the hypothesis that the knowledge both of the biotic and abiotic components of the scenery and their interrelations allows a better understanding of the environmental dynamic, this dissertation had as objectives to characterize the savanna communities' arboreal stratum floristically and phytosociologically, concerning their richness, phytosociological structures and diversity; to identify floristic groupings through varied statistical techniques, representing them by dendrograms; to select species which are really able to make discrimination among the groups; to obtain some discriminant functions to allow classification and reclassification of specimen units, in the groups, to which they have more probability of belonging; to analyze and to characterize the obtained groups; to determine the patterns of distribution of the species of trees by the analysis of correlations of environmental variables with the distribution of the species and plots in the communities being studied; to determine the similarity indexes among the floristic groups and to compare themselves and, finally, to test methods of assorted statistical analysis for application in studies of vegetable communities. Data of vegetation were obtained by the method of multiple plots, with size of 20 X 20 m (400 m2), randomly disposed in each one of the areas being studied. 82 plots were randomly installed. In each one of the 82 patternless units, the circumferences of all the arboreal plants with perimeter to 0,30 m from the level of the soil (PAB) larger or equal to 15,7 cm (DAB 5,0 cm) and the total height of the plants were obtained. In the core of each plot, for determination of the chemical and textural variables of the soil, simple samples of superficial soil were collected (0-30 cm depth). Species were organized according to the families recognized by Angiosperm Phylogeny Group II. The sampling sufficiency was obtained based on the analysis of the curve of the collector. Phytosociological parameters were calculated for each formed group, with the purpose of characterizing them phytosociologically. Having as variables the Index of Covering Value (IVC) of the species, the classification was accomplished by the TWINSPAN (Two-Way Indicator Species Analysis) method, regarding the plots, with the objective of classifying them in floristic groups. The diversity was determined by the Shannon-Wienner and the Simpson Index. The discriminant analysis was undertaken through the STEPWISE method. Considering the matrix of presence and absence of the species in the groups, the floristic similarity was calculated among the groups by the Sorensen Index. To evaluate the hypothesis of the correlation existence between the distribution of the species and environmental variables, the canonical correspondence analysis was accomplished (CCA). The test of permutation of Monte Carlo was applied to verify the importance of the correlations between the emerging distribution patterns of the species and the environmental variables in final CCA. To determine the responsible environmental factors for the distribution of the species, the analysis of regression logistics was used. The Forward Stepwise (Wald) method was used for the sequential selection of the variables. By the species-area curve, it could be observed that, from the plot 75 (30.000 m2 out of the area used as sample), the curve is stabilized with the occurrence of 114 species in the 82 studied plots, distributed between 81 genera and 36 botanical families. The families better represented were Fabaceae, Myrtaceae and Vochysiaceae. The alpha diversity from the arboreal vegetation found in the area being studied was of 4,033 considering the Shannon-Wiener Index and of 0,975 considering the Simpson Index, representing a great floristic diversity. The divisions generated by the classification through the TWINSPAN method separated the plots into four groups: Group 1 Myrcia albo-tomentosa Camb. Association; Group 2 Pterodon emarginatus Vog. Association ; Group 3 Curatella americana L. Association; and Group 4 Qualea multiflora Mart. Association. In the discriminant analysis, 100% of the plots were classified correctly in the Groups 1, 2, 3 and 4, indicating precision of the grouping technique used. The largest similarity could be observed in the Groups 2 and 3, whose Sorensen Index was close to 1 (0,7310). In the four floristic groups, Fabaceae, Myrtaceae, Vochysiaceae, Annonaceae and Apocynaceae families were the most representative floristically in terms of genera and species. In CCA the correlations of the environmental variables with the first ordination axis were, in decreasing order of absolute values, saturation for aluminum, altitude s.n.m., saturation of bases, saturation for magnesium, relationship magnesium/potassium, saturation for hydrogen, potassium tenor, pH(H2O) and relationship calcium/potassium. The saturation for calcium variable presented very weak correlation with the first axis, however, with the second ordination axis, it was very strong. In the diagram of ordination of the plots, the four floristic groups were discriminated in sections different from the diagram, reinforcing their visualization as much defined habitats and with composition of particular species, resulting in clear separation of the four soil classes previously identified. The logistic regression analysis was useful to prove the results obtained from CCA, concerning the environmental variables which determined the distribution of the indicative species of the floristic groups in the studied communities.